Systematic review and meta-analysis of the effect of adverse childhood experiences (ACEs) on brain-derived neurotrophic factor (BDNF) levels. (May 2023) - Vyas, Neha; Wimberly, Courtney E.; Beaman, M. Makenzie; Kaplan, Samantha J.; Rasmussen, Line J.H.; Wertz, Jasmin; Gifford, Elizabeth J.; Walsh, Kyle M.
Abstract: There is continued interest in identifying dysregulated biomarkers that mediate associations between adverse childhood experiences (ACEs) and negative long-term health outcomes. However, little is known regarding how ACE exposure modulates neural biomarkers to influence poorer health outcomes in ACE-exposed children. To address this, we performed a systematic review and meta-analysis of the impact of ACE exposure on Brain Derived Neurotrophic Factor (BDNF) levels - a neural biomarker involved in childhood and adult neurogenesis and long-term memory formation. Twenty-two studies were selected for inclusion within the systematic review, ten of which were included in meta-analysis. Most included studies retrospectively assessed impacts of childhood maltreatment in clinical populations. Sample size, BDNF protein levels in ACE-exposed and unexposed subjects, and standard deviations were extracted from ten publications to estimate the BDNF ratio of means (ROM) across exposure categories. Overall, no significant difference was found in BDNF protein levels between ACE-exposed and unexposed groups (ROM: 1.08; 95 % CI: 0.93–1.26). Age at sampling, analyte type (e.g., sera, plasma, blood), and categories of ACE exposure contributed to high between-study heterogeneity, some of which was minimized in subset-based analyses. These results support continued investigation into the impact of ACE exposure on neural biomarkers and highlight the potential importance of analyte type and timing of sample collection on study results. Highlights: We review 22 articles exploring how adverse childhood experiences impact BDNF levels. Most studies focused on childhood physical, sexual, and emotional abuse. Most studies evaluated subjects with a diverse set of neuropsychiatric disorders. Meta-analysis provides no evidence of ACE-associated changes in BDNF levels. Consensus on the ACE-BDNF relationship remains limited by heterogeneous study designs.